Contemporary interventions in historic fabric: context and authenticity in the work of Gabriel Fagan - Scurr, Michael John (Division of Geomatics, 2015)
This study focuses on three projects by Gabriel Fagan, one of South Africa’s most respected and awarded architects, namely The Dias Museum in Mossel Bay, the SA Breweries Visitor’s Centre in Newlands and the University of Cape Town’s Institute of Infectious Disease and Molecular Medicine. These projects are all essentially contemporary interventions in historic fabric and each contains easily identifiable and iconic new portions – the sail-like roof of the Dias Museum, the glass lift shaft at SAB and the circular glazed pavilion at UCT’s Medical School.